Learning with computers : analysing productive interaction - Littleton, Karen; Light, Paul (Routledge, 1999)
"Learning with Computers brings together a significant body of research that shows how working with others at the computer can be beneficial to learners of all ages, from the early school years to the highest levels of education. Karen Littleton and Paul Light also investigate factors such as gender that explain why some interactions are not as productive as others. The contributors draw upon a considerable range of theoretical frameworks, encompassing cognitive-developmental psychology, social psychology and contemporary situated learning approaches, focusing throughout on the role of the computer in supporting and mediating learning." "Learning with Computers will be of great interest to students and researchers in psychology, as well as those in the rapidly developing field of learning technology."--Jacket